Case report: Preliminary response to tislelizumab plus S-1 in patients with metastatic gallbladder carcinoma: A report of five cases and a literature review - Zhang, Yuzhu; Liu, Yuchen; Liu, Jing; Liu, Tiande; Xiong, Hu; Li, Wen; Fu, Xiaowei; Zhou, Fan; Liao, Shousheng; Fang, Lu; Liang, Bo (Frontiers in Immunology, 2023)
Gallbladder cancer (GBC) and cholangiocarcinoma are common cancers of the biliary system and are associated with a poor prognosis. Surgery and chemotherapy provide limited benefit to patients with advanced biliary tract carcinoma. Novel immunotherapies and molecularly targeted therapies are more effective options; however, few patients benefit and drug resistance is a concern. Here, we report five cases of advanced GBC with either high programmed death-ligand 1 (PD-L1) expression or a high tumor mutation burden (TMB-H). The patients were treated with a combination therapy of tislelizumab and S-1. The tumors were effectively controlled in most patients. One patient developed immune-related pneumonia (irP) during treatment, which resolved after hormone therapy, and the patient underwent surgery. Tislelizumab and S-1 were administered again after surgery; however, recurrent irP required discontinuation, and the tumor progressed after drug withdrawal. These cases demonstrate that combined therapy of anti-programmed cell death protein-1 (PD-1) antibodies and S-1 is a safe and effective regimen with few side effects for GBC patients, especially for sensitive populations (patients with TMB-H, microsatellite instability, deficient mismatch repair, or high expression of PD-L1). To our knowledge, this is the first time that tislelizumab in combination with S-1 has been used to treat patients with advanced GBC.